Proxémie d'apprentissage - Sofiane Issaadi; Alain Jaillet
This paper deals with the relationship between education and space through a proxemics analysis of classroom interactions. Specifically, it is a question of studying the impact of certain spatial variables such as positioning, distance or disposition on the behavior of students in the context of university teaching in an experimental classroom: SpaceTech. Filmed observations were made with a device of collecting and then processed, encoded to statistically treat the observable behavior of the 115 students. The results obtained, allowed the identification of correlations between the choice of occupancy of class space, the one that the teacher occupies and the learning behavior of the students.